1991
DOI: 10.1063/1.104406
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of mirror temperature in GaAs/AlGaAs quantum well laser diodes with segmented contacts

Abstract: A serious problem of high-power GaAs/AlGaAs laser diodes is the strong mirror heating, which is caused by the carrier density and the correlated nonradiative surface recombination at the cleaved mirrors. Therefore the top electrode was segmented in three parts and the influence of a separate controllable potential in the mirror region on the temperature has been studied. The local temperature was measured using spatially resolved Raman scattering. A substantial reduction of the mirror temperature is possible b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Extra processes such as InGaP-or ZnSe-epitaxy [42,49] are applied as well. Additional methods for increasing the COD threshold are: -Non-injecting mirrors [14,[50][51][52][53]. This approach relies on the reduction of the current density (and thus carrier concentration) at the front facet.…”
Section: Robustness Of Diode Lasers Against Codmentioning
confidence: 99%
“…Extra processes such as InGaP-or ZnSe-epitaxy [42,49] are applied as well. Additional methods for increasing the COD threshold are: -Non-injecting mirrors [14,[50][51][52][53]. This approach relies on the reduction of the current density (and thus carrier concentration) at the front facet.…”
Section: Robustness Of Diode Lasers Against Codmentioning
confidence: 99%
“…This important finding is in excellent agreement with former results obtained by other authors for QW lasers. 8,10,20 Surface currents are the most likely explaination. 1,2,8,10,20 Diode lasers with a QD active layer offer a variety of advantages compared to conventional devices such as QW lasers.…”
Section: Discussionmentioning
confidence: 99%
“…One of the convenient method for obtaining the temperature at the laser facet with a relatively high local spatial (1pm) resolution is the micro Raman spectroscopy [1][2][3][4]. Facet heating results from nonradiative' recombination of carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical field (E-100 V/cm) in our experiments was not sufficiently great for initiation so large frequency shifts (AaTO -6 cm1 GaAs-like mode ; AoTO= -3 cm-1 , &oLO= -3cm1 for AlAs-like modes) and for the description of experimental results with traditional theory of selection rules changes in electrical fields (see, for example [10}).For interpretation of our results we used theoretical results of P. Kocevar's work[1 1], where was shown that under sufficiently high electric or photoexcitation of charge carriers in semiconductors noticeable nonequilibrium distributions are to be expected for those phonons, which most strongly couple to the carriers and whose non electronic dissipation rates are slower or comparable to their interaction rates with the carriers. In [1 1] was shown that the fulfilment of the conditions: VcosIl > S (acoustic phonons),(1) Vcosfl > kB® / q (optical phonons),…”
mentioning
confidence: 99%